Objects and interiors - Hanna, Ayn, author; Orman, Jack L., advisor (Colorado State University. Libraries, 1992)
I am attracted to the object/mechanical forms of typewriters, vacuums, lanterns and irons because they are part of my personal world and they have an implied human presence. I see them not only as figurative, but also as feminine. Their general shapes/forms, complicated mechanisms, implied energy and associations with traditionally assigned feminine work all suggest a human quality in both form and content. Their raw nakedness and complete self-containment suggest qualities that I associate with the imagery of goddesses from the ancient Paleolithic time period; a time when our society was matriarchal in nature and the goddess image contained both feminine and masculine attributes. In a sense, these objects become my goddess imagery. I use them as subjects because I feel able to exude my own energy and personality through them. There is an expressive quality to these forms that goes beyond my personal response to them. I am also intrigued by these objects on an abstract, visual level. Their shapes, the materials they are made from and the configurations of how they are put together attract me from a formal, visual standpoint. The objects' implied energy, sense of volume and beauty are all part of the aesthetic attraction as well. The interior spaces are images that come from the environments which I inhabit and the sense of security/safety I feel while inhabiting such. Because they are personal spaces, I try to simplify the forms into basic shapes and play with a flattened three-dimensional space that often includes multiple perspectives. I try to use color and form that, in a personal way, express my feelings about each particular environment.
Keywords: Symbolism in art; Symmetry (Art)